Método para determinação do desempenho de cooperativas de reciclagem - Fidelis, Reginaldo (2017)
In developing countries, Recyclable Material Collectors Cooperatives are presented as a public policy model for managing Urban Solid Wastes with Recyclable Potential (MSWRP) being fundamentals in the resources recovery chain. Thus, this study aims to propose a method to help analyze the management performance of cooperatives in their Operational Activities in the Recycling Chain (OARC): in the waste collection management, in production management, in waste marketing management and as an instrument of social inclusion, income generation and MSWRP reduction. To exemplify the application of the method, a longitudinal research was carried out on some characteristics of cooperatives based in a medium-sized city of Brazil in their OARC. For data treatment were used the DEA-SBM and DEA-Window Models, Tobit Regression, Kruskal-Wallis test, AHP and SAW method. The results suggest that the integrated performance indexes of cooperatives present variability in the scenarios analyzed (economic, environmental and social aspects), indicating that the preferences of a decision maker change the indexes and performance ranking of cooperatives. Furthermore, the results indicate that cooperatives are heterogeneous, with different levels of management performance and administrative organization, besides that presenting communication difficulties, and the rent paid by the collection centers for the collection trucks are very different, in some cases there is a cooperative organized with separated administrative sectors and in others all administrative functions are performed by the of the president of the same. Results also indicate the need for maintenance and increases of public actions thereby integrating the cooperatives and waste collectors, aiming to guarantee greater control in the collection, production and commercialization of MSWRP, since increases in cooperatives management performances in their OARC is fundamental for their survival and for the improvement of its member’s life quality.